Ethnic differences in oro‐facial somatosensory profiles—quantitative sensory testing in Chinese and Danes. (26th August 2013) - Yang, G.; Luo, Y.; Baad‐Hansen, L.; Wang, K.; Arendt‐Nielsen, L.; Xie, Q.‐F.; Svensson, P.
Summary: Ethnic differences in pain experiences have been widely assessed in various pathological and experimental conditions. However, limited sensory modalities have been described in previous research, and the affective‐motivational factors have so far been estimated to be the main mediator for the ethnic differences. This study aimed to detect the ethnic differences of oro‐facial somatosensory profiles related to the sensory‐discriminative dimension in healthy volunteers. The standardised quantitative sensory testing battery developed by the German Research Network on Neuropathic Pain was performed bilaterally in the infraorbital and mental regions on age‐ and gender‐matched healthy Chinese and Danes, 29 participants each group. The influences of ethnicity, gender and test site on the somatosensory profile were evaluated by three‐wayanova . The ethnic disparities were also presented by Z ‐scores. Compared to Danes, Chinese were more sensitive to thermal detection, thermal pain, mechanical deep pain and mechanical pain rating parameters ( P  < 0·002) related to small fibre functions. However, the inverse results were observed for mechanical tactile modality related to large fibre function ( P  <   0·001) and wind‐up ratio ( P  =   0·006). Women presented higher sensitivity compared to men. The mean Z ‐scores of all the parameters from Chinese group were in the normal zone created by Danish Caucasians' means and SDs. The ethnic disparities in somatosensory profile illustrated the necessity of establishing the reference data for different ethnic groups and possibly individual pain management strategies for the different ethnic groups.